Professional iOS database application programming - Patrick, Alessi
Updated and revised coverage that includes the latest versions of iOS and Xcode Whether you're a novice or experienced developer, you will want to dive into this updated resource on database application programming for the iPhone and iPad. Packed with more than 50 percent new and revised material - including completely rebuilt code, screenshots, and full coverage of new features pertaining to database programming in iOS 6 - this must-have book intends to continue the precedent set by the previous edition by helping thousands of developers master database application programming. Shows you how to store data using SQLite, model and manage data using Core Data, and integrate with Web Services Explains how to take advantage of the built-in capabilities of the iPhone Details techniques for integrating iPhone applications into enterprise class systems Encourages you to take advantage of multi-core processors, store data in the cloud, and use storyboards to develop the UI for your app By the end of the book, you will be able to confidently implement a data driven application for the iPhone and integrate an iPhone application within an existing enterprise system